The effect of non-structural components and lignin on hemicellulose extraction. (August 2016) - Liu, Kai-Xuan; Li, Hong-Qiang; Zhang, Jie; Zhang, Zhi-Guo; Xu, Jian
Highlights: Corn stover contains a variety of non-structural components. Water combined with ethanol extraction can remove more non-structural components. Lignin removal helps obtaining low-color value hemicellulose. Non-structural components and lignin removal all improve hemicellulose quality. Abstract: As the important structural component of corn stover, hemicellulose could be converted into a variety of high value-added products. However, high quality hemicellulose extraction is not an easy issue. The present study aims to investigate the effects of non-structural components (NSCs) and lignin removal on alkaline extraction of hemicellulose. Although NSCs were found to have a minimal effect on hemicellulose dissolution, they affected the color values of the hemicellulose extracts. The lignin limited the hemicellulose dissolution and increased the color value by binding to hemicellulose molecules and forming lignin–carbohydrate complexes. Sodium chlorite method can remove about 90% lignin from corn stover, especially the lignin connected to hemicellulose through p-coumaric and ferulic acids. Which increased the hemicellulose dissolution ratio to 93% and reduced the color value 14–28%, but the cost is about 20% carbohydrates lost.